Dilemmas of Tax Competition and Tax Optimisation - Michal SOSNOWSKI (Communications of International Proceedings, 2022)
In the age of globalisation, economic development is increasingly determined by international economic competitiveness, including the tax burdens. Tax systems are one of the basic instruments for managing the national economy. Based on the review of relevant scientific publications, this paper discusses the tax competition between countries in the context of the tax optimisation by transnational corporations seeking to reduce the tax burden. It manifests itself in the relocation of business, in the phenomenon of transfer pricing, or even escapes to tax havens. The inability to legally optimise taxes often prompts unfair taxpayers to operate in the shadow economy. All this is possible and easier also due to the process of the ongoing globalisation of economic activity. For this purpose, the paper focuses on the impact of the tax system on the economic activity of enterprises. To this end, content analysis methods were used in the research, and many fundamental trends and phenomena in the development of the examined theory of taxation were identified. The research results can be used to analyse the interactions between the tax policy and the real economic sphere to intensify economic activity and achieve a competitive advantage in the international arena. The conclusion states that a low tax burden may constitute an essential factor in stimulating investments in a country with a mild tax regime, job creation, dynamic economic growth, and increased enterprises’ competitiveness.
Keywords: competitiveness; globalisation; relocation; shadow economy taxation; tax competition; tax burden; tax optimisation; tax policy; transfer pricing.